Analysis of Factors Affecting the Welfare of Salt Farmers' Households in Donggobolo Village - Indah Purnamasari; Fajrin Hardinandar; Khas Sukma Mulya (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to examine the effects of marketing channels, selling prices, market distance, and customer relationships on the household welfare of salt-farming households in Donggobolo Village, Woha District, Bima Regency, with farmers' income serving as the mediating variable. This study employed a quantitative associative research design to examine the effects of marketing channels, selling prices, market distance, and customer relationships on the household welfare of salt-farming households, with farmers' income serving as the mediating variable, using data collected from 52 salt farmers in Donggobolo Village, Woha District, Bima Regency. Primary data were obtained through structured questionnaires, while secondary data were collected from official statistical reports and relevant publications, with all variables measured using a five-point Likert scale and analyzed using SPSS. The data were analyzed through descriptive statistics, validity and reliability tests, classical assumption tests, multiple linear regression, path analysis, the Baron and Kenny mediation approach, Sobel tests, t-tests, and F-tests to evaluate the direct and indirect relationships among the study variables. Based on the findings, this study concludes that marketing channels, selling price, market distance, and customer relationships significantly influence the welfare of salt-farming households, with farmers' income playing a central mediating role. Customer relationships were identified as the strongest determinant of farmers' income, while income itself was the most influential factor affecting household welfare, and selling price also exerted a significant positive direct effect on welfare. The mediation analysis confirmed that farmers' income fully mediates the relationship between customer relationships and household welfare, highlighting income as the primary pathway through which effective marketing relationships improve living standards. Overall, the study reinforces the importance of strengthening customer relationships, improving pricing mechanisms, and enhancing market-oriented strategies as key approaches to achieving sustainable welfare improvements for salt-farming households in Donggobolo Village.